(untitled) (Orinoquia, 2016)
Oil exploitation in the Gulf of Mexico has reduced coastal fishing areas, so aquaculture can be a labor alternative. To evaluate the susceptibility of cultivation, wild specimens of Lutjanus griseus and L. analis, from a coastal area of Paraiso, Tabasco, were used. In the Marine Aquaculture Station (EAM) of the Academic Division of Biological Sciences (DACBiol) Juarez Autonomous University of Tabasco (UJAT), broodstock lots of both species were formed. The fish were distributed by species in 12,6 m3 tanks (4 m Ø). To determine growth of the organisms from each lot, monthly samplings were conducted, recording the weight and total length from all the fish. Throughout the study, fish were fed four times a day to apparent satiation, using mostly Skretting® marine fish feed and occasionally Pedregal® trout feed. Total water exchanges were made three times a week to maintain water quality. Daily pH, salinity and dissolved oxygen were recorded; nitrates, nitrites and ammonium were measured once a week. From October 2015 to May 2016, L. griseus had an average gain per organism of 7.54 cm and 108.4 g, while L. analis gained on average 14.86 cm and 221.04 g. The contrast of slopes for the association between weight and length indicates that both species presented a statistically similar growth pattern (p = 0.09). The choice of the most suitable species will depend on other parameters such as survival, because even though L. analis obtained better average growth, its survival was 37.5% while in L. griseus reached 66.67%.